Menuju Gereja Elastis: Sintesis antara Gereja Intergenerasi dari Menconi dengan Konsep Gereja Orang Basudara dari Gereja Protestan Maluku - Alakaman, Marlen Tineke (Indonesian Journal of Theology, 2024)
The 21st-century church faces both opportunities for growth and significant ministerial challenges that demand thoughtful response. While many contemporary churches continue to operate within categorical, formalistic models characterized by routine practices, these approaches often prove insufficient for addressing modern church issues. This study examines the intersection of Peter Menconi’s concept of the intergenerational church and the Gereja Protestan Maluku’s (GPM) indigenous notion of Gereja Orang Basudara (“The Brethren Church”). The article proposes the development of new church characteristics, namely, an “elastic church” model that is participatory, embraces the Other (Liyan), and is missional. This research aims to offer an alternative model for church life within GPM.